Mitochondrial genome architecture in non-alcoholic fatty liver disease - Sookoian, Silvia Cristina (2016)
Non‐alcoholic fatty liver disease (NAFLD) is associated with mitochondrial dysfunction, a decreased liver mitochondrial DNA (mtDNA) content, and impaired energy metabolism. To understand the clinical implications of mtDNA diversity in the biology of NAFLD, we applied deep‐coverage whole sequencing of the liver mitochondrial genomes. We used a multistage study design, including a discovery phase, a phenotype‐oriented study to assess the mutational burden in patients with steatohepatitis at different stages of liver fibrosis, and a replication study to validate findings in loci of interest. We also assessed the potential protein‐level impact of the observed mutations. To determine whether the observed changes are tissue‐specific, we compared the liver and the corresponding peripheral blood entire mitochondrial genomes. The nuclear genes POLG and POLG2 (mitochondrial DNA polymerase‐γ) were also sequenced. We observed that the liver mtDNA of patients with NAFLD harbours complex genomes with a significantly higher mutational (1.28‐fold) rate and degree of heteroplasmy than in controls. The analysis of liver mitochondrial genomes of patients with different degrees of fibrosis revealed that the disease severity is associated with an overall 1.4‐fold increase in mutation rate, including mutations in genes of the oxidative phosphorylation (OXPHOS) chain. Significant differences in gene and protein expression patterns were observed in association with the cumulative number of OXPHOS polymorphic sites. We observed a high degree of homology (∼98%) between the blood and liver mitochondrial genomes. A missense POLG p.Gln1236His variant was associated with liver mtDNA copy number. In conclusion, we have demonstrated that OXPHOS genes contain the highest number of hotspot positions associated with a more severe phenotype. The variability of the mitochondrial genomes probably originates from a common germline source; hence, it may explain a fraction of the ‘missing heritability’ of NAFLD.